Penerapan Sistem Informasi Pendaftaran pada TK Aba Kampung Padang Berbasis Web - Laurensa, Ayu; Gultom, Manorang; Tendean, Sandi (Manna wa Salwa Foundation (Yayasan Manna wa Salwa), 2025)
By utilizing the use of website-based technology can provide convenience for schools in the registration process and class data processing. The author uses a descriptive method as a research design. Data collection techniques by conducting interviews, observations and literature study. In addition, the technique used in designing the system in this research is to use object-oriented techniques with modeling Unified Modeling Language (UML). The results of this study are a website-based registration information system at Cahaya Berseri Kindergarten which is used to facilitate the online registration process and make it easier for admins to manage classes and make it easier to print class reports. The conclusion is that the existence of this proposed system can facilitate the registration process, class arrangement and homeroom placement to be more effective and efficient. Suggestions from the authors of the proposed system are developing a system by creating features for registration payments, developing a system so that the website looks more attractive, developing a class arrangement system and homeroom placement for large numbers of students, keeping confidential information on the website safe so that avoiding fraud that can harm certain parties and maintaining the website so that there are no errors in the system